Emerging mechanomedicines informed by mechanotransduction along the integrin–cytoskeleton–nucleus axis - Yuka Yokoyama; Nya Domkam; Hannaneh Kabir; Abdullah Mansour; Shingo Tsukamoto; Ghafar Yerima; Taiji Adachi; Mohammad R. K. Mofrad (APL Bioengineering)
Mechanical forces are fundamental to the formation of normal biological tissues and the maintenance of physiological health. These forces are transmitted from the extracellular environment to the cell interior through cell–cell and cell–ECM interactions, the cytoskeleton, the LINC complex, the nuclear pore complex, and chromatin, ultimately regulating gene expression via transcription factors. This process, known as mechanotransduction, enables cells to convert mechanical signals into biochemical responses. Due to its critical role in various cellular functions and its influence on disease progression, mechanotransduction emerges as a potential therapeutic target for a range of conditions, including cancer and cardiovascular diseases, by integrating it with biochemistry, molecular biology, and genetics. Mechanomedicine, a burgeoning field, seeks to harness insights from mechanobiology to develop innovative diagnostic and therapeutic strategies. By targeting the molecular and cellular mechanisms underlying mechanotransduction, mechanomedicine aims to create more effective and precise treatments. Despite the potential, current clinical practices largely depend on conventional therapies like chemotherapy, underscoring the challenges of manipulating mechanotransducive pathways within living organisms. This review bridges fundamental mechanotransduction mechanisms with emerging therapeutic approaches, highlighting how mechanomedicine can revolutionize clinical practice. It explores the latest advancements in targeting mechanotransducive elements, discusses the therapeutic efficacy demonstrated in preclinical and clinical studies, and identifies future directions for integrating mechanobiological principles into medical treatments. By connecting basic mechanobiology with clinical applications, mechanomedicine holds the promise of offering targeted and reliable treatment options, ultimately transforming the landscape of disease management and patient care.